2022
DOI: 10.1021/acsami.1c17415
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Mimicking Polymer Nanoparticles Targeting CD169+ Macrophages as Long-Acting Nanocarriers for Combination Antiretrovirals

Abstract: Monosialodihexosylganglioside (GM3)-presenting lipid-coated polymer nanoparticles (NPs) that recapitulate the sequestration of human immunodeficiency virus-1 (HIV-1) particles in CD169+ virus-containing compartments (VCCs) of macrophages were developed as carriers for delivery and sustained release of a combination of two antiretrovirals (ARVs), rilpivirine (RPV) and cabotegravir (CAB). RPV and CAB were co-loaded into GM3-presenting lipid-coated polylactic acid (PLA) and poly­(lactic-co-glycolic acid) (PLGA) N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…The NPs remain localized at or close to the cell surface in regions that are enriched in CD169 and that do not overlap with the lysosome marker LAMP-1, with Pearson correlation coefficients of R = 0.65 and 0.19, respectively. These observations imply that GM3-CD169-mediated binding of GM3-NPs to Raji B/CD169 cells avoids triggering an endolysosomal uptake, as is the case for CD169 + DCs and macrophages that collect GM3-NPs in nonendolysosomal VCCs. …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The NPs remain localized at or close to the cell surface in regions that are enriched in CD169 and that do not overlap with the lysosome marker LAMP-1, with Pearson correlation coefficients of R = 0.65 and 0.19, respectively. These observations imply that GM3-CD169-mediated binding of GM3-NPs to Raji B/CD169 cells avoids triggering an endolysosomal uptake, as is the case for CD169 + DCs and macrophages that collect GM3-NPs in nonendolysosomal VCCs. …”
Section: Resultsmentioning
confidence: 87%
“…Human immunodeficiency virus 1 (HIV-1) utilizes GM3-CD169-mediated binding to access nonendolysosomal compartments in macrophages and DCs, called virus-containing compartments (VCCs), which enhance HIV-1 transmission to T cells. We have shown previously that GM3-presenting, lipid-coated gold and polymer NPs (GM3-NPs) bind to CD169-expressing macrophages and DCs and that GM3-NPs colocalize with CD169 + subcapsular macrophages in lymph nodes in vivo . The intracellular fate of GM3-NPs in CD169 + macrophages was found to be affected by the mechanical stiffness of the NP core, but gold or high-molecular-weight polylactic acid (PLA, molecular weight (Mw) = 209 000) NPs with sizes in the range between 80–150 nm successfully reconstituted HIV-1-like properties, including CD169-dependent capture and selective enrichment of NPs in VCC-like compartments in myeloid cells. Intriguingly, GM3-presenting Au NPs were shown to accumulate at the interface between DCs and CD4 + T cells . However, it remains experimentally untested (i) whether GM3-NPs that bypass endocytosis remain accessible to T-cell surface functionalities when sequestered in VCCs of APCs, and (ii) if ligands associated with the NPs can activate T cells at the APC/T-cell interface.…”
mentioning
confidence: 99%
“…Studies showed that cluster of differentiation (CD)169 expression on the surface of Siglec1 macrophages can recognize and bind to monosialodihexosylganglioside (GM3) in the HIV-1 membrane to facilitate the virus propagation [ 39 , 40 ]. Inspired by HIV-1, Eshaghi et al [ 41 ] have developed GM3-presenting, two antiretrovirals (ARVs), rilpivirine (RPV), and cabotegravir (CAB)-loaded, lipid-coated polylactic acid (PLA) and poly (lactic-co-glycolic acid) (PLGA) nanoparticles. The results showed that the virus-mimicking nanoparticles could not only target Siglec1 macrophages but also achieve long-inhibition lasting up to 35 days.…”
Section: The Classification Of Bioinspired Nanostructured Systemsmentioning
confidence: 99%
“…Polymeric nanoparticles (PNPs) and copolymer-based nanocarriers have proven to be promising methods of TMZ delivery. These are solid colloidal particles ranging in size from 100 to 200 nm, capable of targeted transportation of the captured drug into the tumor [ 76 , 77 , 78 ]. These systems can be obtained naturally and synthetically, and one of them—a polymer based on lactic-co-glycolic acid (PLGA)— is approved by the USFDA.…”
Section: Nanoscale Delivery Systemsmentioning
confidence: 99%